Pyrolysis of mangaba seed: Production and characterization of bio-oil. (November 2015) - Santos, Roberta M.; Santos, Aglaéverton O.; Sussuchi, Eliana Midori; Nascimento, Juciara S.; Lima, Álvaro S.; Freitas, Lisiane S.
Highlights: Use mangaba seed to transformation in bio-oil by pyrolysis process. Study of the variables process of pyrolysis for the mangaba seed: temperature, sample mass and prior heating. Characterization of the mangaba seed used as biomass in pyrolysis process. The bio-oil of mangaba seed showed the presence of hydrocarbons, acids and phenols. Abstract: The aim of this study was to evaluate the potential of Hancornia speciosa GOMES (mangaba) seeds as a novel matrix for the production of bio-oil. The study was divided into three steps: (i) characterization of the biomass (through elemental analysis (CHN), infrared spectroscopy (FTIR-ATR), thermogravimetry (TG), and determination of biomass composition; (ii) pyrolysis of mangaba seed to obtain the bio-oil; and (iii) characterization of the bio-oil (thermogravimetry and gas chromatography/mass spectrometry-GC/qMS). The TG of the sample showed a mass loss of around 90% in 450 °C. In the pyrolysis experiments the variables included temperature (450 and 600 °C), sample mass (5 and 11 g) and prior heating (with or without), with the best conditions of 600 °C, 11 g of seeds and prior heating of the furnace. The GC/qMS analysis identified carboxylic acids and hydrocarbons as the major components, besides the presence of other compounds such as furanes, phenols, nitriles, aldehydes, ketones, and amides.